(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the scientific evidence on health actions proposed in Transition of Care Programs for the elderly. The scope chosen for this study was an integrative review. The search strategy was carried out in the Virtual Health Library portal - which incorporates LILACS, BDENF and IBECS; as well as MEDLINE, SCOPUS, Embase and Web of Science, with controlled descriptors and non-controlled descriptors (key words) that were used to locate the articles. The searches occurred in the month of January 2021. The sample of articles elected for this integrative review was composed of 37 articles, with the years 2015 (n = 4), 2016 (n = 5), 2018 (n = 5), 2019 (n = 6) and 2020 (n = 5) being the years with the highest number of publications. As for the databases, no articles were found eligible in the VHL portal, which encompasses LILACS, IBECS and BDENF, to the detriment of the other bases in which the articles of this review were chosen, being them: Scopus (n = 12), Embase (n = 5), Web Of Science (n = 13), and Medline (n = 7). Transitional care programs for the elderly directly impact on improved medication adherence, better healthy lifestyles, and better clinical indicators, as well as lower rates of adverse events and hospital readmission, through health actions such as: patient and caregiver education while still in the hospital environment; telephone and home follow-up after discharge; medication supervision and management; and creation of individual therapeutic plans aimed at nutritional, physical, and cognitive rehabilitation.